Diversity, antifungal and plant growth promoting activity of actinomycetes from rhizosphere soils of medicinal plants - GANGWAR, M; KATARIA, H (The Indian Journal of Agricultural Sciences, 2026)
A total of 202 actinomycete isolates were obtained from 25 medicinal plant rhizosphere soils. These isolates belonged to Streptomyces (n = 175), Saccharopolyspora (n = 13), Micromonospora (n = 7), Noardia (n = 3), Pseudonocardia (n = 3) and Actinomadura (n = 1) spp. The highest number and diversity of actinomycetes were isolated from Curcuma longa L. rhizosphere soil (2.7 × 105/g). Eleven isolates displayed antagonistic activity against at least one of the eight phytopathogenic fungi tested. Fifty isolates exhibited indole-3-acetic acid (IAA) production in the range of 10.2-93.8 µg/ml. Forty seven isolates were able to solubilize phosphorus in the range of 0.02- 0.68 mg/ml. Seventeen isolates produced the amount of catechol-type siderophore ranging between 2.68-51.6 µg/ml. While all the 22 isolates produced hydroxamatetype siderophores ranging from 8.71-144.21 µg/ml. These results confirm that rhizospheric soils of medicinal plants represent an extremely rich reservoir for the isolation of significant diversity of actinomycetes that are potential sources for the discovery of biologically active compounds.